Inventory Management Analysis in Creating Corporate profits - Ahmad, Hamzah (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This research was conducted at PT. Ade Sultra Persada which is located on Jl. Y. Wayong ByPass Lepo-lepo, Kendari, Southeast Sulawesi. The object of this research is inventory management in creating profit that uses in addition to the period order quantity method, it also uses the last-in-first-out (LIFO) method. Sources of data used are observations and interviews of tax and accounting staff. Secondary data sources are income statements and cash flow statements, lists of assets, depreciation, and annual tax returns. The analytical method used in this research is descriptive analysis. inventory management PT. Ade Sultra Persada The gas station unit is not in accordance with the applicable Organizational Work Procedures (TKO). The fuel supply storage depot must be strategically located, in order to avoid flooding like several years ago, to anticipate the occurrence of losses caused by the fuel distribution pipe not being managed properly, it is still necessary to check periodically to avoid fuel evaporation caused by the pipe, when to fill up supplies. The fuel in the depot has not been controlled properly, resulting in the company experiencing losses or decreasing profits due to evaporation